Expression of Toll-like receptor and cytokine mRNAs in feline odontoclastic resorptive lesion (FORL) and feline oral health. (20th December 2022) - Thomas, Sheeba; Lappin, David F.; Spears, Julie; Bennett, David; Nile, Christopher; Riggio, Marcello P.
Abstract: Feline odontoclastic resorptive lesion (FORL) is a common chronic inflammatory condition whose aetiopathogenesis remains unclear. FORL affects 20–75% of cats and causes excruciating pain and tooth loss. The purpose of this study was to evaluate chronic inflammation in FORL by assessing differences in Toll-like receptor (TLR) and cytokine transcripts in gingival tissues between diseased and healthy cats. Gingival tissue samples were collected from 14 healthy cats with no known clinical signs of oral disease and 41 cats with FORL. Levels of mRNA encoding TLR2, TLR3, TLR4, TLR7, TLR9 and the cytokines interleukin-1β (IL-1β), IL-4, IL-6, IL-10, IL-12, interferon-γ (IFN-γ) and tumour necrosis factor-α (TNF-α) was evaluated using quantitative real-time PCR. Statistical significance of the results was assessed using non-parametric tests. Levels of TLR and cytokine transcripts were upregulated in gingival tissue from cats with FORL as compared with healthy gingival tissue: TLR2, TLR3 and TLR9, p  ≤ 0.001; TLR4 and TLR7, p  ≤ 0.01; IFN-γ, IL-4, IL-6, IL-10, IL-12, IL-1β and TNF-α, p ≤ 0.001). In conclusion, expression of TLR and both pro- and anti-inflammatory cytokines were significantly increased, confirming an ongoing chronic inflammatory response to the microbiome in FORL. It is likely that dysbiosis of the oral microbiota in cats with FORL activates the innate immune response, leading to active inflammation that results in tooth resorption. Highlights: First study to investigate TLR expression in FORL. Expression of TLR2, TLR3, TLR4, TLR7 and TLR9 significantly increased in FORL. Expression of pro-and anti-inflammatory cytokines increased in FORL.